Orthogonal test design for optimization of the extraction of polysaccharide from Paeonia sinjiangensis K.Y. Pan - Tian, Shuge (Medknow Publications, 2011)
BACKGROUND: Paeonia sinjiangensis K.Y. Pan is a perennial herb belonging to the ranunculaceae family and it is one of the most important crude drugs in traditional Chinese medicine. In this article, Paeonia sinjiangensis K.Y. Pan rich in polysaccharide is used as an experimental material. MATERIALS AND METHOD: Study the effects of proportion, temperature, times and time taken for the extraction yield of polysaccharide through a single-factor exploration. Then, through an orthogonal experiment (L(9)(3)(4)), it was investigated to get the best extraction conditions. RESULTS: The results showed that the ratio of solvent to raw material, number of extractions and duration of extraction were the main variables that influenced the yields of extracts. The separation procedure of precipitation with alcohol and the purification from the removing proteins were deeply analyzed. Meanwhile the contents of polysaccharide were determined by anthrone colorimetry. CONCLUSION: The highest yield was obtained when the ratio of solvent to raw material, number of extractions, and duration of extraction were 8:1, 2, and 1.5 h, respectively. The content of soluble polysaccharide is 51.57%.